Simple broadband via‐free microstrip composite right and left hand transmission line. Issue 9 (4th April 2016) - Shen, Qiusheng
Abstract : A novel simple broadband via‐free microstrip composite right and left hand transmission line (CRLH‐TL) is proposed by etching a straight‐line slot in the conductor of the microstrip line and an eight‐edge‐shaped slot on the ground below the straight‐line slot. The CRLH‐TL has the advantages of simple structure, smaller size, and wide left hand frequency band. The results show that the left hand frequency band of the CRLH microstrip transmission line is 4.91−6.09 GHz, and the left hand frequency bandwidth is 1180 MHz.